Short-range ordering in a battery electrode, the ‘cation-disordered’ rocksalt Li1.25Nb0.25Mn0.5O2 - Jones, Michael A; Reeves, Philip J; Seymour, Ieuan D; Cliffe, Matthew J; Dutton, Siân E; Grey, Clare P (Chemical communications (Cambridge, England), 2019)
Cation order, with a local structure related to γ-LiFeO2, is observed in the nominally cation-disordered Li-excess rocksalt Li1.25Nb0.25Mn0.5O2via X-ray diffraction, neutron pair distribution function analysis, magnetic susceptibility and NMR spectroscopy. The correlation length of ordering depends on synthesis conditions and has implications for the electrochemistry of these phases.